Gods and angels - Park, David 1953- (Bloomsbury Publishing, 2016)
A powerful new collection from the critically-acclaimed, prize-winning author David Park
Keywords: Short stories; Northern Ireland / Fiction; FICTION / Short Stories (single author); Englisch; Erzählung; Northern Ireland; Fiction